ANALISIS BIAYA DAN MANFAAT USAHA WISATA TERUMBU KARANG TAMAN PENDIDIKAN LAUT BINTANG SAMUDERA - Aldiansyah Hari Friatno; Baru Sadarun; Nurdiana A (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2014)
The purpose of this study were to analysic the costs incued in the management of coral reefs in the Garden tour Education of Ocean Bintang Samudra, to know the benefits derived from coral reef business tourism and the feasibility of reef tourism business in TPL BS Konawe Southeast Sulawesi in order to provide sustainable economic benefits. This research was carried out in September to October 2013. Data was collected through direct observation and depth interviews to tourists and management of TPL BS related economic activity in reef tourism activities. Research results obtained that the total cost incurred in the management of coral reefs tourism in the TPL BS Rp191.566.665. Gains from reef tourism business is Rp313.433.335, obtained from the reduction of total cost and total benefit derived from such business